YtrASa, a GntR-Family Transcription Factor, Represses Two Genetic Loci Encoding Membrane Proteins in Sulfolobus acidocaldarius - Lemmens, Liesbeth; Tilleman, Laurentijn; De Koning, Ezra; Valegård, Karin; Lindås, Ann-Christin; Van Nieuwerburgh, Filip; Maes, Dominique; Peeters, Eveline (Frontiers in Microbiology, 2019)
In bacteria, the GntR family is a widespread family of transcription factors responsible for the regulation of a myriad of biological processes. In contrast, despite their occurrence in archaea only a little information is available on the function of GntR-like transcription factors in this domain of life. The thermoacidophilic crenarchaeon Sulfolobus acidocaldarius harbors a GntR-like regulator belonging to the YtrA subfamily, encoded as the first gene in an operon with a second gene encoding a putative membrane protein. Here, we present a detailed characterization of this regulator, named YtrASa, with a focus on regulon determination and mechanistic analysis with regards to DNA binding. Genome-wide chromatin immunoprecipitation and transcriptome experiments, the latter employing a ytrASa overexpression strain, demonstrate that the regulator acts as a repressor on a very restricted regulon, consisting of only two targets including the operon encoding its own gene and a distinct genetic locus encoding another putative membrane protein. For both targets, a conserved 14-bp semi-palindromic binding motif was delineated that covers the transcriptional start site and that is surrounded by additional half-site motifs. The crystallographic structure of YtrASa was determined, revealing a compact dimeric structure in which the DNA-binding motifs are oriented ideally to enable a specific high-affinity interaction with the core binding motif. This study provides new insights into the functioning of a YtrA-like regulator in the archaeal domain of life.